Tempering implementation optimism: distinguishing between efficacy and effectiveness in implementation research - Per Nilsen; Jeanette Wassar Kirk; Katarina Ulfsdotter Gunnarsson; Kristin Thomas (Implementation Science Communications)
Abstract Background The distinction between efficacy (performance under ideal conditions) and effectiveness (performance in real-world settings) is well established in intervention research. Intervention effectiveness is often used as a proxy for implementation readiness. However, relying on this assumption can lead to overly optimistic expectations about real-world outcomes if the complexities of routine practice settings are not adequately considered. Main body This paper introduces the distinction between implementation efficacy (implementation strategy performance under controlled or highly supported conditions) and implementation effectiveness (performance under typical, resource-constrained settings). We argue that the efficacy–effectiveness distinction is as critical for implementation research as it is for intervention research. Recognizing and systematically operationalizing this distinction can sharpen conceptual clarity, strengthen research design and enhance the relevance and generalizability of findings for real-world application. Yet despite its importance, this distinction is rarely made explicit in implementation studies. Research often fails to specify the conditions under which implementation strategies are investigated; studies can vary widely in how closely they reflect routine practice. Compounding this issue, economic evaluations remain uncommon in implementation research. However, without systematic assessment of resource use, it is difficult to determine whether reported implementation outcomes have been achieved through contextually feasible strategies or through intensive supports, such as dedicated staffing, external facilitation, or financial incentives, which are rarely available in everyday practice. To address this gap, we propose adapting the PRECIS-2 (Pragmatic Explanatory Continuum Indicator Summary 2) framework from clinical trials into an “Implementation PRECIS” tool. An adapted version of PRECIS-2 for implementation research could offer a systematic way to describe the extent to which a study reflects idealized conditions versus real-world practice. Conclusion Clarifying whether implementation strategies are studied under efficacy-like or effectiveness-like conditions enhances research design, interpretation, and communication with stakeholders. It also supports informed decisions about replication and scale-up. By embracing this distinction, implementation research can temper overly optimistic assumptions, better reflect real-world constraints, and contribute more meaningfully to evidence-based practice. We argue that making this distinction explicit is a necessary step toward a more pragmatic and transparent science of implementation.